Oral health care practice of women with pregnancy experience - Suwargiani, Anne Agustina; Arief, Erry Mochamad; Aripin, Dudi; Widyaputra, Sunardhi; Susilawati, Sri (Universitas Padjadjaran, 2020)
Introduction: Oral health of pregnant women is essential due to the physiological, psychological, and immune response changes. Oral health-related prenatal services, however, are still insufficient. There are some deficiencies in health care and health promotion activities provided for pregnant women. The purpose of this study was to determine the oral health care practice of women with pregnancy experience. Methods: A cross-sectional descriptive study was conducted towards Indonesian women with pregnancy experience—sample size calculation was conducted using the survey population to estimate the population proportion formula. Inclusion criteria were women with pregnancy experience, owns mobile phones, able to access the Google® Form questionnaire, and willing to take part in the study. Exclusion criteria were women with pregnancy experience who did not complete the Google® Form questionnaire and women who were having a miscarriage or stillborn. Sampling technique was performed using the non-probability sampling with consecutive sampling technique in August until September 2019. Data collection using questionnaire in form of Google® Form questionnaire and distributed online to women who has pregnancy experience throughout Indonesia. Results: The respondents were grouped in three age categories: 22-34 years, 35-44 years, and 45-65 years. Respondents came from 45 cities throughout Indonesia. 62.70% of pregnant women had never visited the dentist. Pregnant women who have visited the dentist were only 37.30%. Pregnant women visited the dentist because they experience a toothache, while the reason for most pregnant women did not visit the dentist because they dd not have any oral health complaints. Conclusion: 62.70% of pregnant women had never visited the dentist. Pregnant women who have visited the dentist were only 37.30%. Women with pregnancy experience mostly have oral health care to treat their oral health complaints. However, the majority of them never visits the dentist because they did not have any oral health complaints.